Urgensi Pendidikan Islam Nonformal; Madrasah Diniyah Takmiliyah Awwaliyah (MDTA) di Kota Medan Sumatera Utara - Nuristiqamah Awaliyahputri B (Jurnal Pendidikan Islam, 2023)
This study aims to describe the urgency of one of the nonformal Islamic education, namely Madrasah Diniyah Takmiliyah Awwaliyah (MDTA). This type of research is qualitative descriptive research carried out in several non-formal Islamic educational institutions; Madrasah Diniyah Takmiliyah Awwaliyah (MDTA) in Deli Serdang Regency, Medan, North Sumatra. Data were obtained through observation at Madrasah Diniyah Takmiliyah Awwaliyah (MDTA) and further information through interviews. The results of this study explain that the existence of Madrasah Diniyah Takmiliyah Awwaliyah (MDTA) will greatly influence the religious aspects of society in the city of Medan. If the city of Medan is known as one of the metropolitan cities in Indonesia and its people are very diverse, be it religion, culture, ethnicity, language, race, and others, it cannot be separated from the strong foundation of community religious education through nonformal Islamic education. Some of the urgency of nonformal Islamic education at Madrasah Diniyah Takmiliyah Awwaliyah (MDTA), include: 1) Completion of religious learning obtained at school; 2) Providing provision of religious knowledge from an early age; 3) Printing children to be perfect human beings; 4) Guiding and educating children as the next generation; 5) Increasing public awareness of religious education; and 6) Teaching children about the importance of learning religion.